Analisis Potensi Kegagalan Jenis Defect Dominan Pada Transmission Case Dan Clutch Housing Menggunakan Metode FMEA-TOPSIS - Dzikri, Daffa Amara; Nurhasanah, Nunung (Universitas Al Azhar Indonesia, 2023)
PT. Mitsubishi Krama Yudha Motors and Manufacturing Engine Factory, or PT. MKM 1 manufactures the TD-4V21 engine for canters and engine parts such as crankcase and timing gear, transmission, front axle, and differential case. This research was conducted at PT. MKM 1 on the Transmission Case and Clutch Housing production line aims to identify the dominant type of defect, analyze the potential causes of failure using the Failure Mode Effect and Analysis (FMEA) method, and determine the priority causes of failure to be repaired using the Technique for Others Reference by Similarity to the method. Ideal Solution (TOPSIS). In the production of TMTD & CLH, there are three dominant types of defects based on the application of the Pareto diagram, namely, the result of the NG thread process is 42%, the hole diameter plus-minus is 23%, and the outspent position is 13%. There are causes of failure that need to be addressed based on the analysis of the Ishikawa diagram and the application of the FMEA-TOPSIS method. In the results of the NG thread process, the causes of failure that need to be overcome are the wrong settings for tools, parts, or materials that are not smooth, there are iron ores. On the defect hole diameter plus-minus, try ex tool insert, loose bolt insert tool, and overspec tool dimension. While the outspent position there are causes of failure that need to be overcome, namely the length of the part over, improvements to the-axisscale, and panel brackets that are accidentally turned off.Keywords – Quality improvement, FMEA, TOPSIS, Diagram Ishikawa, Failure Mode Effect And Analysis, Technique For Others Reference By Similarity To Ideal Solution.